Antimicrobial peptide LL37 is potent against non-growing Escherichia coli cells despite a slower action rate - Salimeh Mohammadi; Derek Saucedo; Sattar Taheri-Araghi (mSphere)
ABSTRACT Antimicrobial peptides (AMPs) have long been considered as potential agents against non-growing, dormant cells due to their membrane-targeted action, which is largely independent of the cell’s growth state. However, the relationship between the action of AMPs and the physiological state of their target cells has been unclear, with recent reports offering conflicting views on the efficacy of AMPs against bacteria in a stationary phase. In this study, we employ single-cell approaches combined with population-level experiments to examine the action of human LL37 peptides against Escherichia coli cells in different growth phases. Time-lapse, single-cell data from our experiments reveal that LL37 peptides act faster on large, dividing cells than on small, newborn cells. We extend this investigation to non-growing E. coli cells in a stationary phase, where we observe that the action of LL37 peptides is slower on non-growing cells compared to exponentially growing cells. This slower action rate is, however, not mirrored in the minimum bactericidal concentration (MBC) measurements. Notably, we find that the MBC for non-growing cells is lower than for exponentially growing cells, indicating that, given sufficient time, LL37 peptides exhibit strong potency against non-growing cells. We propose that the enhanced potency of LL37 peptides against non-growing cells, despite their slower action, can be attributed to continuous absorption of AMPs on the cell membrane over time.IMPORTANCEAntibiotic treatments can fail because of the regrowth of a bacterial subpopulation that resumes proliferation once the treatment ceases. This resurgence is primarily driven by non-growing, dormant bacterial cells that withstand the action of antibiotics without developing resistance. In this study, we explore the potency of the human antimicrobial peptide LL37 against non-growing Escherichia coli cells. Our findings reveal that despite a slower initial action, LL37 peptides, given sufficient time, demonstrate strong efficacy against non-growing cells. These insights suggest a potential role of antimicrobial peptides in combating persistent bacterial infections by targeting the non-growing cells.